The Countervailing Effects of Weight Stigma on Weight-Loss Motivation and Perceived Capacity for Weight Control. (September 2020) - Major, Brenda; Rathbone, Joanne A.; Blodorn, Alison; Hunger, Jeffrey M.
We hypothesized that exposure to weight stigma simultaneously increases motivation to lose or avoid gaining weight to avoid future stigma and decreases perceived capacity to do so, by heightening concerns about experiencing stigma and negative affect. Study 1 showed that more frequently experiencing weight-based discrimination was associated with greater concerns about being a victim of weight stigma, which predicted increased motivation to lose weight but decreased perceived capacity for weight control. Study 2 showed that participants randomly assigned to view a weight-stigmatizing (vs. control) message showed increased concerns about being a target of weight stigma, which indirectly increased motivation to lose weight and decreased state self-control. These, in turn, predicted increased willingness to engage in unhealthy weight-loss behaviors and decreased perceived capacity for weight control, respectively. Study 3 showed that increased motivation to avoid stigma and increased negative affect mediate these effects of exposure to weight stigma.